Discovery of novel aporphine alkaloid derivative as potent TLR2 antagonist reversing macrophage polarization and neutrophil infiltration against acute inflammation - Junjie Yang; Yue Pan; Xiaoshan Zeng; Shuwen Liu; Zhipeng Chen; Kui Cheng (Acta Pharmaceutica Sinica B, 2023)
Toll-like receptor 2 (TLR2) mediated macrophages regulate the protective immune response to infectious microorganisms, but the aberrant activation of macrophages often leads to pathological inflammation, including tissue damage. In this study, we identified antagonists of TLR2 by screening 2100 natural products and subsequently identified Taspine, an aporphine alkaloid, as an excellent candidate. Furthermore, analysis of the 10 steps chemical synthesis route and structural optimization yielded the Taspine derivative SMU-Y6, which has higher activity, better solubility, and improved drug-feasible property. Mechanistic studies and seq-RNA analysis revealed that SMU-Y6 inhibited TLR2 over other TLRs, hindered the formation of TLR2/MyD88 complex, and blocked the downstream NF-κB and MAPK signaling pathway, thus suppressing the release of inflammatory cytokines. SMU-Y6 could stabilize TLR2 and bind to TLR2 protein with a Kd of 0.18 μmol/L. Additionally, SMU-Y6 could efficiently reverse the M1 phenotype macrophage polarization, reduce the production of cytokines as well as infiltration of neutrophiles and alleviate the local inflammation in mice with acute paw edema and colitis. Collectively, we reported the first aporphine alkaloid derivative that selectively inhibits TLR2 with high binding affinity and superior drug-feasible property, thus providing an urgently-needed molecular probe and potential drug candidate for inflammatory and autoimmune disease therapy.